1988
DOI: 10.1002/bjs.1800750225
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in tropical pancreatitis

Abstract: Surgery in tropical pancreatitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 8 publications
1
14
1
Order By: Relevance
“…However, it is possible that the 2 patients who avoided follow-up may have done so because of persistence of pain. Our data are in concordance with previous studies in TCP patients, where pain relief was observed in 80%-90% of patients after LPJ [21][22][23]. It implies that elevated ductal pressure plays an important role in the pathogenesis of pain in this entity.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is possible that the 2 patients who avoided follow-up may have done so because of persistence of pain. Our data are in concordance with previous studies in TCP patients, where pain relief was observed in 80%-90% of patients after LPJ [21][22][23]. It implies that elevated ductal pressure plays an important role in the pathogenesis of pain in this entity.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study demonstrated high morbidity and mortality associated with conventional LPJ in this group of patients [14]. In contrast, in our series, there was no mortality and no major morbidity.…”
Section: Discussioncontrasting
confidence: 82%
“…The incidence ofketosis is 20% in Congo and 18% in Kerala [1]. (4) The most striking difference, however, is that while the occurrence of pancreatic cancer as a sequel or complication of calcific pancreatitis is not reported from Africa, the association between the 2 conditions is well established in Kerala, and many workers in this field are of the opinion that there is a causal relationship between the 2 conditions [7,9,11,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Gross. The pancreas is usually described as being firm, fibrous, and gritty to the touch [1][2][3][4][5][6][7][8][9][10][11]; however, it is important to recognize that acute lesions--either edema, fatty necrosis, or hemorrhagic necrosis--are sometimes superimposed on chronic pancreatitis [11,17,19]. It is believed that these acute lesions occur less frequently and disappear as pancreatic insufficiency develops [18,19].…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation